Efektivitas Pembuktian Unsur Melawan Hukum dalam Pasal 2 dan Pasal 3 Undang-Undang Tindak Pidana Korupsi - Guruh Hidayat (Badan Penerbit STIEPARI Press, 2024)
The unlawful elements in Articles 2 and 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption are legal elements that are complex and open to multiple interpretations. These elements not only encompass violations of legal regulations but also violations of the general principles of good governance (AUPB) and standards of propriety in the exercise of public power. This study aims to conduct an in-depth analysis of the effectiveness of proving the unlawful element in criminal corruption trials, as well as to identify the obstacles and legal strategies used by law enforcement officials. The research method used is a normative legal method, with a legislative approach. The first discussion focuses on the differences in the characteristics of the unlawful element in Article 2, which is a formal offence, and Article 3, which is a material offence, as well as their consequences for proof in court. The second discussion outlines the various technical and legal obstacles faced by public prosecutors in proving these elements, including difficulties when there is no written violation of the law, as well as strategies for proving through non-legalistic approaches such as expert opinions on governance and proof through the principles of propriety and substantive justice. The research findings indicate that the effectiveness of proving the element of unlawfulness is highly dependent on the flexibility of judicial interpretation and the courage of law enforcement officials in exploring the values of substantive justice. Therefore, it is recommended that the Supreme Court develop technical guidelines for proving the element of unlawfulness in corruption crimes to ensure legal certainty and consistency in judicial practice